Indicators to assess physiological heat strain – Part 3: Multi-country field evaluation and consensus recommendations. Issue 3 (3rd July 2022) - Ioannou, Leonidas G.; Tsoutsoubi, Lydia; Mantzios, Konstantinos; Vliora, Maria; Nintou, Eleni; Piil, Jacob F.; Notley, Sean R.; Dinas, Petros C.; Gourzoulidis, George A.; Havenith, George; Brearley, Matt; Mekjavic, Igor B.; et al.
ABSTRACT: In a series of three companion papers published in this Journal, we identify and validate the available thermal stress indicators (TSIs). In this third paper, we conducted field experiments across nine countries to evaluate the efficacy of 61 meteorology-based TSIs for assessing the physiological strain experienced by individuals working in the heat. We monitored 372 experi-enced and acclimatized workers during 893 full work shifts. We continuously assessed core body temperature, mean skin temperature, and heart rate data together with pre/post urine specific gravity and color. The TSIs were evaluated against 17 published criteria covering physiological parameters, practicality, cost effectiveness, and health guidance issues. Simple meteorological parameters explained only a fraction of the variance in physiological heat strain (R 2 = 0.016 to 0.427; p < 0.001), reflecting the importance of adopting more sophisticated TSIs. Nearly all TSIs correlated with mean skin temperature (98%), mean body temperature (97%), and heart rate (92%), while 66% of TSIs correlated with the magnitude of dehydration and 59% correlated with core body temperature (r = 0.031 to 0.602; p < 0.05). When evaluated against the 17 published criteria, the TSIs scored from 4.7 to 55.4% (max score = 100%). The indoor (55.4%) and outdoor (55.1%) Wet-Bulb Globe Temperature and the Universal Thermal Climate Index (51.7%) scored higher compared to other TSIs (4.7 to 42.0%). Therefore, these three TSIs have the highest potential to assess the physiological strain experienced by individuals working in the heat.